Favourable prognostic role of regression of primary melanoma in AJCC stage I–II patients. (December 2013) - Ribero, S.; Osella‐Abate, S.; Sanlorenzo, M.; Savoia, P.; Astrua, C.; Cavaliere, G.; Tomasini, C.; Senetta, R.; Macripò, G.; Bernengo, M.G.; Quaglino, P.
Summary Background The prognostic significance of regression in primary melanoma has been debated over the past few years. Once it was considered to be a negative prognostic factor, as it may have prevented proper melanoma thickness measurement, therefore affecting the staging of the tumours. For this reason, it was considered to be an indication for sentinel lymph node biopsy (SLNB) in melanoma < 1 mm. Objectives To ascertain the utility of SLNB in thin melanoma and to clarify the role of regression in disease‐free survival (DFS) and overall survival (OS) in our series. Methods We analysed data collected from 1693 consecutive patients with AJCC (American Joint Committee on Cancer) stage I–II melanoma. Results Globally, SLNB was performed in 656 out of 1693 patients. Regression was present in 349 patients and 223 of them were characterized by thin lesions. SLNB was performed in 104 cases of thin melanoma with regression. The majority of regional lymph node metastases were observed in patients who did not undergo SLNB (89 out of 132). Among the remaining 43 'false negative' patients only three showed regression in the primary. Using the Cox multivariate model, histological regression maintained a significant protective role [hazard ratio (HR) 0·62, P = 0·012 for DFS; HR 0·43, P = 0·008 for OS] when corrected for the principal histopathological and clinical features, despite SLNB. Conclusions We confirmed that regression alone should not be a reason to perform SLNB in thin melanoma and, on the contrary, it can be considered a favourable prognostic factor in patients with AJCC stage I–II melanoma.